Math, asked by subhamitasil6, 6 months ago

simplify 4(8x-13)+2(9x-11) =3(5x-7)-17​

Answers

Answered by Anonymous
2

Step-by-step explanation:

4(8x - 13) + 2(9x - 11) = 3(5x - 7) - 17 \\  \\ 32x - 52 + 18x - 22 = 15x - 21 - 17 \\  \\  = 14x - 74 = 15x - 38 \\  \\  =  - 74 + 38  = x \\  \\  = x = ( - 36)

Answered by NewGeneEinstein
1

Step-by-step explanation:

\\ \sf\hookrightarrow 4(8x-13)+2(9x-11)=3(5x-7)-17

\\ \sf\hookrightarrow 32x-52+18x-22=15x-21-17

\\ \sf\hookrightarrow 32x+18x-52-22=15x-38

\\ \sf\hookrightarrow 50x-74=15x-38

\\ \sf\hookrightarrow 50x-15x=-38+74

\\ \sf\hookrightarrow 35x=36

\\ \sf\hookrightarrow x=\dfrac{36}{35}

Similar questions